INVESTIGATIONS ON THE VITAMIN-A AND BETA-CAROTENE CONTENT OF BLOOD-PLASMA IN INFERTILE COWS - GUL, Y; CAN, R; YILMAZ, K (M H Schaper Gmbh Co Kg, 1988)
In this research, 5 heifers and 5 cows of Brown-Swiss Breed, at two-nine years of age, were used. Analyses of vitamin A and beta-carotene were made monthly from samples taken during one year period. In clinical examinations, endometritis in four cows and ovarian cysts in two cows were diagnosed. In other animals infertility was observed during this study period. Vitamin A and beta-carotene levels were measured monthly during the pasture and cowshed period. Averages of vitamin A and beta-carotene in cowshed period were 47.05 .+-. 2.22 .mu.g/100 ml and 98.47 .+-. 28.60 .mu.g/100 ml, respectively. These averages for pasture period were calculated 44.14 .+-. 7.70 .mu.g/100 ml and 464.79 .+-. 121.75 .mu.g/100 ml. The values of beta-carotene in cowshed period were below 100 .mu.g/100 ml which is accepted deficiency for fertility by authors. The difference between the averages of beta-carotene content in cowshed and pasture period was found statistically significant (p < 0.01).